(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This paper explores the process of self-reflection undertaken by a History lecturer with a view to promoting the same type of critical awareness among a group of third- year History students at a South African university. The study draws on student experiences of and responses to a critical pedagogy that offered a deconstruction of past identities and enabled an emerging discourse of agency with contemporary relevance. By means of a qualitative methodological approach, openended, reflective questionnaires were used amongst a focus group to gauge student perspectives. The paper concludes that via creative and innovative pedagogy, History can become a vehicle for promoting self-awareness and in turn critical citizenship in South Africa’s current social context.